Small-scale irrigation and household wages relationship: Proof from Deder district, Ethiopia (International Journal of Irrigation and Water Management, 2014)
Investment in irrigation development is an important strategy in reducing risks associated with rainfall variability and achieving food security. This study examines the link between small-scale irrigation and household income. It also presents inherent institutional challenges in water allocation and the unintended outcomes. It used cross-sectional data obtained using a sample of 150 respondents selected through multi-stage sampling techniques from Deder district in eastern Ethiopia in 2009/2010 cropping year. The data were analyzed using Heckman-two step econometric models. The probit estimation shows that sex of the household head, access to credit and extension services have significant positive effect whereas the financial constraints restrains participation in irrigation water utilization. The ordinary least square using household income as outcome variable reveals that credit access, livestock holdings and proportion of land allocated to irrigation have significant positive effect on household income. This indicates that the more land is allocated to irrigation the higher will be the income. Moreover, the study pointed out that local institutional failure was a more important challenge than hydrological factors in managing the irrigation system. This has a policy implication in terms of strengthening the institutional environment.